At the Center of the Storm : My Years at the CIA - Tenet, George, 1953- and Harlow, Bill, 1950- (New York Harper Collins Publisher, 2007)
Tenet's memoir of his life at the CIA--a revelatory look at the inner workings of America's top intelligence agency and its dealings with national leaders at home and abroad. Tenet illuminates how the country was prepared--and not prepared--to deal with a world full of new and deadly threats. Beginning with his installation as Director in 1997, he unfolds the events that led up to 9/11: his declaration of war on Al Qaeda in 1998, CIA operations inside Afghanistan, the worldwide operational plan to fight terror, his warnings to White House officials in the spring and summer of 2001, and the plan for a response laid down just six days after the attack. In his narration of the run-up to the war in Iraq, Tenet provides fresh insights and background. Finally, he offers his thoughts on the future of U.S. intelligence and its role in foreign-policy decisions.--From publisher description
Include Colour illustration, Glossary and Index
Keywords: United States -- Intelligence officers -- United States. Central Intelligence Agency -- Employees -- Diplomatic relations -- September 11 Terrorist Attacks (2001)